Determination of HMGB1 in hepatitis B virus-related acute-on-chronic liver failure patients with acute kidney injury: Early prediction and prognostic implications - Liu, Yu; Yuan, Wei; Fang, Miao; Guo, Hongying; Zhang, Xin; Mei, Xue; Zhang, Yuyi; Ji, Longshan; Gao, Yating; Wang, Jiefei; Qian, Zhiping; Li, Man; et al. (Frontiers in Pharmacology, 2023)
Background: Acute kidney injury (AKI) is a frequent complication in patients with hepatitis B virus-related acute-on-chronic liver failure (HBV-ACLF) and is associated with high rates of mortality. We aimed to estimate serum high mobility group protein 1 (HMGB1) levels in hepatitis B virus-related acute-on-chronic liver failure patients and analyze their clinical value in the development and outcomes of Acute kidney injury. Methods: A total of 251 consecutive patients with hepatitis B virus-related acute-on-chronic liver failure were enrolled in this retrospective study. Using the International Club of Ascites staging criteria of Acute kidney injury, 153 patients developed Acute kidney injury. The clinical data of patients were collected and serum levels of high mobility group protein 1 were measured by ELISA. All patients were followed up until death or for a minimum of 3 months. Early prediction and prognostic implications of high mobility group protein 1 in Hepatitis B Virus-Related Acute-on-Chronic Liver Failure Patients with Acute Kidney Injury were investigated in different cohorts, including a propensity score-matched ACLF cohort. Results: Among all individuals with hepatitis B virus-related acute-on-chronic liver failure, the incidence of Acute kidney injury was 61.0% (153/251). The patients who developed stage 2/3 Acute kidney injury showed the highest high mobility group protein 1 levels, followed by those who developed stage 1 Acute kidney injury, and those without Acute kidney injury showed the lowest high mobility group protein 1 levels. Moreover, high mobility group protein 1 levels were significantly higher in non-survivors than in survivors among hepatitis B virus-related acute-on-chronic liver failure patients with Acute kidney injury. Furthermore, analysis of the area under the receiver operating characteristic curve (AUROC) indicated that serum high mobility group protein 1 levels (pre-matching: AUC = 0.740; post-matching: AUC = 0.661) may be a potential predictive factor for Acute kidney injury development and that high mobility group protein 1 (AUC = 0.727) might be a reliable biomarker for prognosis in patients with Acute kidney injury. Conclusion: In patients with hepatitis B virus-related acute-on-chronic liver failure, Acute kidney injury is universal. Acute kidney injury and its stages negatively influence the 90-day transplant-free mortality rate. Serum high mobility group protein 1 levels can serve as a positive predictor of Acute kidney injury development, and high mobility group protein 1 might also be a prognostic biomarker for Acute kidney injury among hepatitis B virus-related acute-on-chronic liver failure patients.